2001
DOI: 10.1074/jbc.m009689200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Increases Growth and Motility of Colorectal Carcinoma Cells

Abstract: Chronic use of nonsteroidal anti-inflammatory drugs results in a significant reduction of risk and mortality from colorectal cancer in humans. All of the mechanism(s) by which nonsteroidal anti-inflammatory drugs exert their protective effects are not completely understood, but they are known to inhibit cyclooxygenase activity. The cyclooxygenase enzymes catalyze a key reaction in the conversion of arachidonic acid to prostaglandins, such as prostaglandin E 2 (PGE 2 ). Here we demonstrate that PGE 2 treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
320
2
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(339 citation statements)
references
References 46 publications
14
320
2
3
Order By: Relevance
“…For example, Apc Δ716/+ mice had fewer gastrointestinal tumors when crossed with EP2 −/− mice [32] and EP2 was necessary for mammary hyperplasia in COX-2 transgenic mice [28]. To our knowledge, there are no reports suggesting that EP3 can transactivate EGFR, but EP4 has been shown to be involved in tumor cell motility [33] and it is over-expressed in tumors from Apc Δ716/+ mice [32]. None of these reports provided a direct link between EP2 or EP4 and EGFR, but combined with our data, they suggest that transactivation of EGFR through these EP receptors might have a role in development of breast and colon cancer and other malignancies.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Apc Δ716/+ mice had fewer gastrointestinal tumors when crossed with EP2 −/− mice [32] and EP2 was necessary for mammary hyperplasia in COX-2 transgenic mice [28]. To our knowledge, there are no reports suggesting that EP3 can transactivate EGFR, but EP4 has been shown to be involved in tumor cell motility [33] and it is over-expressed in tumors from Apc Δ716/+ mice [32]. None of these reports provided a direct link between EP2 or EP4 and EGFR, but combined with our data, they suggest that transactivation of EGFR through these EP receptors might have a role in development of breast and colon cancer and other malignancies.…”
Section: Discussionmentioning
confidence: 96%
“…PGE 2 signaling through the EP4 receptor has previously been associated with colorectal cancer. For example, PGE 2 has been reported to stimulate the proliferation and motility of LS174T colorectal cancer cells via EP4 dependent stimulation of PI-3-K/AKT signaling [10]. In addition Pozzi et al [36] demonstrated EP4 mediated PI-3-K/ ERK signaling pathway in mouse colon carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 treatment was shown to enhance incidence of colonic tumors in AOM-treated rats and attenuates non-steroidal anti-inflammatory drug (NSAID)-induced tumor regression in Apc Min/+ mice by increasing intestinal epithelial cell proliferation and reduction of apoptosis [7][8][9]. In addition, PGE 2 can increase cell survival, invasion, and migration of human colon cancer cells [10][11][12]. Collectively, these in vivo studies strongly implicated a role for elevated levels of PGE 2 in colorectal carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interest was sparked by the fact that COX inhibitors reduced the mortality rate from certain cancer patients [16,17] and that most of the tumors exhibited overexpression of COX-2, a potential oncogene [18]. One of the major COX-2 derived products, PGE 2 , has also been shown to induce the growth, migration, and invasiveness of carcinoma cells [19]. In view of the fact that PGE 2 up-regulates the expression of COX-2 in several cancer cell lines resulting in positive feedback actions of PGE 2 [20,21], we hypothesize that another COX-2 derived down-stream product with similar mitogenic activity, TXA 2 , will be also capable of inducing the expression of COX-2.…”
Section: Introductionmentioning
confidence: 99%